2022
DOI: 10.1177/10283153221091623
|View full text |Cite
|
Sign up to set email alerts
|

Developing Global Competence in Global Virtual Team Projects: A Qualitative Exploration of Engineering Students’ Experiences

Abstract: The incorporation of digital learning and teaching tools has been recognized as presenting an opportunity to maximize access, quality, and inclusion, especially when it comes to international education. Unanticipated events, such as the COVID 19 pandemic, can result in profound disruptions to teaching and learning, and the use of these tools can provide mitigation to these disruptions. This paper reports on the design and study of an InVEST global virtual team (GVT) program that incorporates global competency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Also, population growth, economic development, and climate change have increased environmental pressures, decreasing air and water quality, and increasing environmental health disparities between the wealthy and the poor (Mihelcic et al, 2017; United Nations, 2020). Global pandemics have required virtual multidisciplinary collaborations among STEM professionals from different countries and cultures (Ndubuisi et al, 2022). These have magnified calls for STEM students to develop global competencies (Ayokanmbi, 2011; Hunter et al, 2006; Jesiek et al, 2014; Majewska, 2022; Mihelcic et al, 2017; Strong et al, 2020; U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Also, population growth, economic development, and climate change have increased environmental pressures, decreasing air and water quality, and increasing environmental health disparities between the wealthy and the poor (Mihelcic et al, 2017; United Nations, 2020). Global pandemics have required virtual multidisciplinary collaborations among STEM professionals from different countries and cultures (Ndubuisi et al, 2022). These have magnified calls for STEM students to develop global competencies (Ayokanmbi, 2011; Hunter et al, 2006; Jesiek et al, 2014; Majewska, 2022; Mihelcic et al, 2017; Strong et al, 2020; U.S.…”
Section: Introductionmentioning
confidence: 99%
“…When they improved the curricula for grades 2-8 and 9-12, the Turkish Ministry of National Education (MoNE, 2017) also embraced the 21st-century skills framework besides values education and necessitated the injection of such global competences as communication in foreign languages, social and civic competences, cultural awareness, and communication. Certain practices and opportunities such as study abroad (see Ozkul, 2019;Schenker, 2019;Fisher et al, 2022), exchange programs, virtual exchange programs (see Duffy et al, 2022;Ndubuisi et al, 2022), and teaching abroad (Cushner & Mahon, 2016) are seen as key means to acquire and develop GC. Such programs are also known to alter students' perspectives of the world and improve their cultural awareness (Cushner & Mahon, 2016) and intercultural competence and abilities (He et al, 2017;Özkan & Mutludoğan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The InVEST study showed that intercultural activities provide a unique lens to students to exhibit intercultural sensitivities to virtual global team projects and can facilitate better collaboration with students from various institutions. The study also suggests that higher education institutions can utilize these learning approaches and enhance their engineering students' skills and instill valuable professional experience for their future roles as modern-day engineers [16].…”
Section: Introductionmentioning
confidence: 91%